2021
DOI: 10.3390/v13101951
|View full text |Cite
|
Sign up to set email alerts
|

Chronic LCMV Infection Is Fortified with Versatile Tactics to Suppress Host T Cell Immunity and Establish Viral Persistence

Abstract: Ever since the immune regulatory strains of lymphocytic choriomeningitis virus (LCMV), such as Clone 13, were isolated, LCMV infection of mice has served as a valuable model for the mechanistic study of viral immune suppression and virus persistence. The exhaustion of virus-specific T cells was demonstrated during LCMV infection, and the underlying mechanisms have been extensively investigated using LCMV infection in mouse models. In particular, the mechanism for gradual CD8+ T cell exhaustion at molecular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 153 publications
(242 reference statements)
2
4
0
Order By: Relevance
“…The humoral immune response mediated by B cells plays a critical role in host defense against a variety of pathogens through secreting antibodies by plasma cells ( 52 , 53 ). In this study, chronic infection elicited more robust germinal center B-cell responses and antibody production than acute infection, consistent with previous studies ( 11 ). Surprisingly, the proportion of MALT B cells in chronic infection was significantly higher than that in acute infection on 8 dpi.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The humoral immune response mediated by B cells plays a critical role in host defense against a variety of pathogens through secreting antibodies by plasma cells ( 52 , 53 ). In this study, chronic infection elicited more robust germinal center B-cell responses and antibody production than acute infection, consistent with previous studies ( 11 ). Surprisingly, the proportion of MALT B cells in chronic infection was significantly higher than that in acute infection on 8 dpi.…”
Section: Discussionsupporting
confidence: 93%
“…With the help of Tfh cells in the light zone of GCs, B cells differentiate into high-affinity antibody-secreting plasma cells and resultant memory B cells ( 55 , 56 ). Consistent with previous studies ( 11 ), our study showed that chronic infection induces a more robust germinal center B-cell response and higher production of antibody-producing plasma cells than acute infection. Overall, the B-cell immune response was more intense in chronic infection; however, it failed to clear the viruses once persistent infection was established, which deserves further exploration.…”
Section: Discussionsupporting
confidence: 93%
“…T‐cell suppression has frequently been used interchangeably with T‐cell exhaustion, causing considerable confusion. T‐cell suppression with decreased T‐cell functionality can be caused by multiple factors, including the influence of cytokines including IL‐10 from dendritic cells and exhausted CD4 T‐cells, interferon‐α and interferon‐β, and TGF‐β secreted by regulatory T‐cells or myeloid‐derived suppressor cells [33,34]. Furthermore, because CD8 T‐cells share several lymphocyte characteristics with NK‐cells, T‐cell suppression is very probable when there is tissue hypoxia (reduced oxygen); neuroendocrine activation; a hypercoagulable state (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…and TGF-β secreted by regulatory T-cells or myeloidderived suppressor cells [33,34]. Furthermore, because CD8 T-cells share several lymphocyte characteristics with NK-cells, T-cell suppression is very probable when there is tissue hypoxia (reduced oxygen); neuroendocrine activation; a hypercoagulable state (e.g.…”
Section: -Cell Suppression Has Frequently Been Used Interchangeably W...mentioning
confidence: 99%
“…The LCMV variant Clone 13 (Cl 13) infection model has been widely used for revealing mechanisms for T cell suppression and virus persistence [ 69 , 70 , 71 ]. Following LCMV Cl 13 infection, virus-specific T cells develop but gradually lose their functionalities, as evidenced by the substantially diminished capabilities to produce antiviral cytokines, such as IFN-γ and TNF-α, to display cytotoxic activity with granzymes and perforin secretion, as well as to proliferate in response to antigenic restimulation.…”
Section: Pathogenic Functions Of Type I Ifnmentioning
confidence: 99%